Effectiveness of perampanel in the treatment of pediatric patients with focal epilepsy and ESES: A single-center retrospective study - Yu, Tao; Teng, Zi-Teng; Liu, Xue-Yan; Wang, Hua (Frontiers in Pharmacology, 2022)
Objective: To investigate the therapeutic effect and influencing factors of perampanel (PER) on electrical status epilepticus during sleep (ESES). Methods: We retrospectively analyzed the clinical data of pediatric patients with focal epilepsy and ESES who were treated at the Epilepsy Center of Shengjing Hospital of China Medical University between January 2016 and March 2022. Changes in the spike wave index (SWI) after 24 weeks of PER add-on treatment were compared. Kaplan‒Meier survival analysis, the log-rank test and multivariate Cox regression analysis were performed. Results: A total of 54 pediatric patients met the inclusion criteria, including 33 males and 21 females. The mean age at the diagnosis of epilepsy was 6.41 ± 2.14 years and at ESES diagnosis was 7.58 ± 2.40 years. The mean ESES duration before add-on PER was 25.31 ± 15.12 months. The mean age of the patients at add-on PER initiation was 9.69 ± 2.12 years. The SWI disappeared in 29 children after 6 months of PER add-on treatment, and the response rate was 53.7%. Univariate analysis with the log-rank test showed that the therapeutic effect of PER differed according to the age at ESES diagnosis and ESES duration before add-on PER treatment. Multivariate Cox regression analysis showed that only ESES duration before PER administration was a risk factor for PER treatment failure, and the other factors had no effect on the therapeutic effect. Conclusion: PER add-on treatment has a good therapeutic effect on ESES and can be used as an alternative to corticosteroid and benzodiazepines. The therapeutic effect of PER add-on treatment was not related to the dose. A longer ESES duration results in a worse therapeutic effect. Therefore, more aggressive treatment measures should be implemented for ESES.